High number of CD14+B7H4+ monocytes is significantly associated with increased concentrations of IL-4, IL-13, IL-10, and TGF-β1 in tumor microcirculation of lung carcinoma - Vuković Jelena (Military Health Department, Ministry of Defance, Serbia, 2021)
Background/Aim. Lung cancer (LC) is one of the leading causes of mortality. Disease progression and advanced disease are characterized by the unprotective immune response due to M2 macrophage polarization, myeloid-derived suppressor cells (MDSC) activity, cytokine imbalance, and regulatory T lymphocyte activity. The aim of this study was to investigate the association between Th1/Th2 cytokines and CD14+B7H4+ monocyte (Mo) number in LC patients. Methods. We investigated principal Th1/Th2 cytokines and CD14+B7H4+ Mo number in blood and tumor microcirculation samples of 41 LC patients (III and IV clinical stage) and 30 healthy participants (control group). Results. The serum concentrations of investigated cytokines in all patients vs. heathy controls did not differ significantly. Stratification in groups according to tumor histology, disease extent, and tumor size revealed significant differences. LC patients with different histology types demonstrated significant differences, both in serum and tumor microcirculation samples. The presence of metastasis was associated with increased IFN-γ/IL-4 in blood and increased IL-13 in tumor microcirculation samples. Tumor microcirculation samples of the largest tumors were characterized by the Th2 cytokine profile. Investigation of CD14+B7H4+ Mo in blood samples demonstrated a significant association of extreme value of this cell population with elevated IL-2/IL-13. Patients with the highest CD14+B7H4+ Mo number in tumor microcirculation samples demonstrated significant increments of IL-4, IL-13, IL-10, and TGF-β1. Conclusion. LC patients demonstrated polarization of cytokine response associated with microenvironment origin, tumor histology type, tumor size, and disease extent. The highest number of CD14+ B7H4+ monocytes is significantly associated with the Th2 cytokine profile.